(untitled) (Journal Of Educational and Psychological Researches, 2025)
This research aims to reveal the perceptions of social studies teachers in the Sultanate of Oman about the digital economy. To achieve the objectives of the study, the descriptive approach was used. The research sample consisted of 488 male and female social studies teachers in the Sultanate of Oman. The data were collected using a questionnaire consisting of 40 items. The research found that there are positive perceptions among social studies teachers in the Sultanate of Oman. The research also revealed the absence of statistically significant differences in the variables of gender, years of experience, and number of training courses. In light of these results, the study recommended the need to provide training courses for teachers on the digital economy and its educational applications, as well as to update social studies curricula to include the concepts of the digital economy. The research came out with some suggestions, including providing digital educational resources in addition to developing sustainable training programs for teachers that keep pace with rapid digital developments, besides studying students’ perceptions to enhance the effectiveness of digital education.